Which Are the Main Surface Disinfection Approaches at the Time of SARS-CoV-2? - Ghedini, Elena; Pizzolato, Marco; Longo, Lilia; Menegazzo, Federica; Zanardo, Danny; Signoretto, Michela (Frontiers in Chemical Engineering, 2021)
Among many guidelines issued by the World Health Organization to prevent contagion from novel coronavirus (SARS-CoV-2), disinfection of animate and inanimate surfaces has emerged as a key issue. One effective approach to prevent its propagation can be achieved by disinfecting air, skin, or surfaces. A thorough and rational application of an Environmental Protection Agent for disinfection of surfaces, as well as a good personal hygiene, including cleaning hands with appropriate products (e.g., 60–90% alcohol-based product) should minimize transmission of viral respiratory pathogens such as SARS-CoV-2. Critical issues, associated with the potential health hazard of chemical disinfectants and the ineffective duration of most of the treatments, have fostered the introduction of innovative and alternative disinfection approaches. The present review aims to provide an outline of methods currently used for inanimate surface disinfection with a look to the future and a focus on the development of innovative and effective disinfection approaches (e.g., metal nanoparticles, photocatalysis, self-cleaning, and self-disinfection) with particular focus on SARS-CoV-2. The research reviews are, usually, focused on a specific category of disinfection methods, and therefore they are limited. On the contrary, a panoramic review with a wider focus, as the one here proposed, can be an added value for operators in the sector and generally for the scientific community.